Petalidium bembeense (Acanthaceae), a new species from Angola and Namibia - Swanepoel, Wessel; Wyk, Abraham E. Van (Phytotaxa, 2026)
Petalidium bembeense, easily confused with P. welwitschii, is described here as a new species. It is a range-restricted species, only known from the Zebra Mountains in Namibia, and the northern extension of this mountain complex across the Kunene River in Angola, within the Kaokoveld Centre of Endemism. It typically grows on plains, hillsides, and along ephemeral riverbeds and drainage lines, mainly in soils derived from anorthosite and gabbro of the Kunene Igneous Complex. Key distinguishing features for P. bembeense include the green to reddish green appearance of the plants, indumentum on stems, petioles and inflorescence branches consisting mainly of multicellular stalked glandular trichomes and on the lamina and bracts stellate-dendritic, bifurcate, trifurcate and dendritic trichomes, interspersed with stalked glandular or simple trichomes. The flowers are borne in racemose dichasia and are notable for a relatively large corolla, lilac or mauve (pale violet) corolla lobes with contrasting paler or white traces (veins). A comparison of key morphological features distinguishing P. bembeense from P. welwitschii, its closest look-alike, is provided. Brief comparisons are also made with P. ohopohense and P. rossmannianum, species with which it was previously confused. Based on IUCN Red List criteria, a provisional conservation status of Endangered (EN) is recommended for the new species.